Răspuns :
a )A ( 2, -2 ) ∈ Gf ⇔ f ( 2 ) = - 2 ⇔ 2-4 = - 2 ( adevarat )
B ( 3, 6 ) ∈ Gf ⇔ f(3)= 6 ⇔ 3-4 = 6 ( fals )
A ( 2, -2 ) ∈ Gf, iar B ( 3, 6 ) ∉ Gf
b ) M ( 1, 2a ) ∈ Gf ⇔ f(1) = 2a ⇔ -3 = 2a ⇔ a = - [tex] \frac{3}{2} [/tex]
B ( 3, 6 ) ∈ Gf ⇔ f(3)= 6 ⇔ 3-4 = 6 ( fals )
A ( 2, -2 ) ∈ Gf, iar B ( 3, 6 ) ∉ Gf
b ) M ( 1, 2a ) ∈ Gf ⇔ f(1) = 2a ⇔ -3 = 2a ⇔ a = - [tex] \frac{3}{2} [/tex]
f(x) = x - 4
a) daca A ∈ grafic, atunci f(2) = -2 ; verifcand se vede ca 2 - 4 = - 2 ⇒
⇒ A ∈ grafic
B ∈ grafic ⇔ f(3) = 6 f(3) = 3 - 4 = - 1 ≠ 6 ⇒ B ∉ grafic
b) M(a,1,2a) ∈ grafic, inseamna ca f(a) = 1,2a a - 4 = 1,2 a = 5,2
a) daca A ∈ grafic, atunci f(2) = -2 ; verifcand se vede ca 2 - 4 = - 2 ⇒
⇒ A ∈ grafic
B ∈ grafic ⇔ f(3) = 6 f(3) = 3 - 4 = - 1 ≠ 6 ⇒ B ∉ grafic
b) M(a,1,2a) ∈ grafic, inseamna ca f(a) = 1,2a a - 4 = 1,2 a = 5,2